Penerapan Pembiasaan Program Keagamaan Dalam Membentuk Karakter Religius Siswa di SMP Islam Mbah Bolong Jombang - M Sulthon Auliyak; Shobihus Surur (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study investigates the influence of religious programs on the formation of religious character of students at SMPI Mbah Bolong Jombang. Education is a human effort to acquire physical and spiritual skills that are in accordance with the values of society and culture. To track the development or behavior of student discipline, SMPI Mbah Bolong Jombang suggests the implementation of religious programs to shape student behavior in accordance with the values applied. In this discussion, the researcher will discuss the influence of habituation of religious programs on the religious character of students. The objectives of the study are 1) To describe the implementation of the implementation of habituation of religious programs at SMPI Mbah Bolong Jombang. 2) To describe how to form the religious character of students at SMPI Mbah Bolong Jombang. 3) To describe the application of habituation of religious programs in shaping the religious character of students at SMPI Mbah Bolong Jombang. This qualitative research studies the subject thoroughly through case studies. Observation, interviews, and documentation are data collection methods. Data analysis is through three, namely reduction, data presentation, and conclusion. The results of the study show that 1) At SMPI Mbah Bolong, religious programs to cultivate students' religious character have been implemented well, starting from daily and weekly activities. 2) Increasing discipline at SMPI Mbah Bolong for various reasons, such as school rules, etc. religious programs at SMPI Mbah Bolong Jombang help students be more disciplined in addition to getting closer to Allah.